Pengaruh Loyalitas Kerja Terhadap Kinerja Karyawan Pada Divisi Operasional PT. BPR Prisma Dana Manado - Philipi Mandiangan; Jacob Makapedua; Vekky Supit (Universitas Merdeka Madiun, 2023)
The author conducted this study to determine how much influence work loyalty has on employee performance at the Operational Division of PT. BPR Prisma Dana Manado. This research was conducted using data collection procedures obtained through observation and questionnaires. In this study, the population that the author made as respondents amounted to 40 people. From the results of research conducted by the author that, work loyalty has a significant effect on employee performance at the Operational Division of PT. BPR Prisma Dana Manado. It can be proven by the Pearson value for the X variable of 0.673 which means that it lies in the Pearson correlations value of 0.61 to 0.80 which means that the level of relationship between work loyalty and employee performance is included in the strong category with a significant value of 0.000 <0.05 meaning correlated or related. To be emphasized again how the relationship and the influence of work loyalty on employee performance is the relationship between work loyalty its influence on employee performance in this study got a value of r = 0.673 which means it has a positive and strong relationship, while the effect of work loyalty on employee performance can be seen from the results of the coefficient calculation. determination of 0.453 and represented by 45.3%. So the influence of loyalty by 45.3% and 54.7% is not known or influenced by factors not examined.